On Rational-Type Contractive Mappings in Bi-Complex Valued Control Metric Spaces and Applications (European Journal of Pure and Applied Mathematics, 2025)
This manuscript studies some unique and common fixed point results in the context of bi-complex valued control metric space(BVCMS) using rational-type inequalities. The presented work explains the idea of BVCMS and then shows the necessary criteria for a pair of contractive type mappings in this space to have common fixed points. To show how applicable our results are,we also give an example. Finally, the existence of solutions of a system of fractional differential equations has been studied using the obtained results.
Keywords: Bi-complex valued controlled metric spaces; Fixed Point; Rational type contractions; Fractional Differential Equations